Marketing Strategy of the Indonesian Tahfizh Daarul Quran on Social Media to Attract the Interest Parents of students - Dina Anggraini (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2021)
Indonesia is one of the countries in the world that has been seriously affected by the Covid-19 Pandemic since 2019. Various problems occur in the economy of the country and society in Indonesia which cause problems in the education aspect. This is felt especially in terms of marketing at the Daarul Quran Indonesia Foundation or better known as DaQu which is a Foundation engaged in the Education industry in which there is a program boarding school that was started in 2003 which was founded by Ust. Yusuf Mansur, located in Kampung Quran, Cipondoh, Tangerang. According to internal data from the Daarul Quran Indonesia Foundation, there has been a 35% decline in student enrollment from 2019-2021. This is based on the decline in the economy of prospective guardians of education costs and the delay in the Daarul Quran Indonesia Foundation using social media as part of its marketing activities. Social media marketing is the use of social media platforms and websites to promote products or services. The Daarul Quran Indonesia Foundation then took action to take advantage of new media as a new opportunity in a highly changing market environment by utilizing the Facebook, Instagram, Youtube and Website platforms as a means of delivering information to the public. Through the campaign movement, 'Santri Indent DP 5 Million' is the solution chosen by the Daarul Quran Indonesia Foundation to increase the number of registrations for students for the New Academic Year. It can be seen from the results of data collection through a questionnaire, that the Santri Indent DP 5 million campaign has an impact on parents' interest in sending their children to the Daarul Quran Indonesia Foundation, and has an impact on increasing the number of students for the 2021/2022 academic year, in addition to social media, especially Instagram. be the best marketing tool in this campaign.